PENGARUH PEMBERIAN PUPUK KOMPOS DAN UREA TERHADAP PERTUMBUHAN BIBIT KAKAO (THEOBROMA CACAO L) - Anis Tatik Maryani; Erlida Ariani; Jumiati ' (Jurnal Sagu, 2011)
Cacao represent one of the potential export commodity.Methods to increase the yield of cacao plants are generative, but the popular method today is the generative because it can yield large amount of cacau seeds.